Construction and optimization strategy of ecological security pattern in a rapidly urbanizing region: A case study in central-south China. (March 2022) - Ding, Mingming; Liu, Wen; Xiao, Li; Zhong, Feixia; Lu, Na; Zhang, Jun; Zhang, Zhihui; Xu, Xianli; Wang, Kelin
Graphical abstract: Highlights: A new strategy to optimize ecological sources and resistance surfaces was proposed to build ESP. The optimal diffusion distance of ecological source was analyzed to meet future needs. Boundary analysis and resistance radial effect were integrated to construct resistance surface. More reasonable ecological corridor direction was obtained for the construction of ESP. Abstract: Rapid urbanization would lead to deterioration of the eco-environment and damage the functioning of ecosystem services. Ecological security pattern (ESP) is one of important national strategies in China for coordinating the ecosystem protection and economic development. Previous studies have mainly focused on how to identify ecological sources and extract ecological corridors, but optimization of the identified ecological sources and resistance surfaces are seldom explored. In this study, a new strategy to optimize ecological sources and resistance surfaces was proposed. The optimal diffusion distance of each existing ecological source with poor landscape connectivity was analyzed to meet future needs. The radial effect of resistance in areas with high resistance values were considered in combination with the characteristics of species migration. Hunan is an important province in the Yangtze River Economic Belt (YREB) and the Rise of Central China strategies. Taking a rapidly urbanizing region in Hunan Province as an example, the results showed that the total area of the optimized ecological sources was 9.60% higher than that of the existing area, which expanded the radial range of ecosystem services and enhanced ecosystem internal connectivity. According to the spatial distribution of important ecological landscape elements, the ecological framework of "two axes, four cores, and four belts" was proposed. This study offers a new insight for ESP construction, which can provide a new reference for ecological protection and development planning of rapidly urbanizing regions in central-south China.